Persistence of transferable oxazolidinone resistance genes in enterococcal isolates from a swine farm in China - Huang, Zheren; Bai, Yilin; Wang, Qin; Yang, Xue; Zhang, Tiejun; Chen, Xuan; Wang, Hongning (Frontiers in Microbiology, 2022)
The appearance of transferable oxazolidinone resistance genes poses a major challenge to public health and environmental safety. These genes not only lead pathogenic bacteria to become resistant to linezolid but also reduce sensitivity to florfenicol, which is widely used in the veterinary field. To verify the dissemination of oxazolidinone resistance genes in enterococcal isolates from pigs at different production stages in a swine farm in China, we collected 355 enterococcal isolates that were resistant to florfenicol from 600 (150 per stage) fresh fecal swabs collected from a swine farm. Through initial PCR screening and whole-genome sequencing, 175 isolates harboring different oxazolidinone resistance genes were identified. All isolates carried the optrA gene. A total of 161 (92%, 161/175) isolates carried only the optrA gene. Three (1.71%, 3/175) isolates carried both the optrA and poxtA genes, and eleven (3.1%, 11/175) isolates contained the optrA gene and poxtA2 and cfr(D) variants. By sequencing the whole genomes, we found that the 161 isolates of E. faecalis belonged to 28 different STs, including 8 new STs, and the 6 isolates of E. faecium belonged to four different STs, including one new ST. The phylogenetic tree based on SNPs of the core genome showed that both clonal spread and horizontal transfer mediated the diffusion of oxazolidone resistance genes in enterococcal isolates at specific stages in pig farms. Moreover, enterococcal isolates carrying oxazolidone resistance genes could spread from breeding pigs to fattening pigs, while transferable oxazolidone resistance genes in enterococcal isolates could persist on a pig farm throughout all production stages. Representative enterococcal isolates with different oxazolidinone resistance genes were further studied through Nanopore sequencing. We identified a novel plasmid, pM4-80L4 (15,008 bp), carrying the poxtA2 and cfr(D) genes in enterococcal isolates at different stages. We also found three different plasmids harboring the poxtA gene with high genetic variation.In addition, four genetically distinct plasmids carrying the optrA gene were identified, and Tn554 was found to mediate chromosome-localized optrA gene transfer. Our study highlighted that transferable oxazolidinone resistance genes in enterococcal isolates could persist throughout all production stages on a pig farm.